Mitigasi Faktor-Faktor Penyebab Cost Overrun pada Proyek Gedung Pendidikan - Turrohmah, Annisa; Adi, Henny Pratiwi; Niam, Moh Faiqun (Universitas Batanghari Jambi, 2025)
Cost overrun is a significant challenge in construction projects, including educational buildings, which results in budget cuts, project delays, and increased maintenance costs. This study analyzes cost overruns on three projects in Central Java: IAIN Kudus Integrated Laboratory Building (1%), UIN Walisongo Mahad Building (2.3%), and Rembang MIN 1 Class Building (10%). These three projects were chosen because they have varying scales of cost increases and different characteristics of educational buildings. The research used quantitative methods with a questionnaire involving 53 respondents from consultants and contractors. Data analysis was carried out by testing validity, reliability, correlation, and dominant factor analysis using SPSS. The research results show that the main factors causing cost overrun are design changes and non-compliance with schedules (0.77), delays in material delivery (0.76), as well as inadequate planning and delays in equipment delivery (0.74). Other factors include ineffective decisions, poor financial management, and suboptimal cost control. Mitigation recommendations include improving the quality of planning, strict cost control, implementing systematic risk management, and utilizing BIM technology to increase estimation accuracy and decision-making efficiency to reduce the risk of cost overrun.